An Enlarged Pragmatist Inquiry Paradigm for Methodological Pluralism in Academic Design Research - Melles, Gavin (Artifact, 2008)
As part of a process of academic legitimization, design has made claims to be epistemologically and methodologically distinct from the Arts and Sciences. Among the multiple propositions that have been made about this distinctiveness little has been said about the fundamentally pragmatic nature of design research and practice. Pragmatism in both instrumental and critical forms is a robust epistemological and methodological terrain for design research, which architecture and built environment disciplines have explored as a basis for their methodological pluralism. In the newer design disciplines of industrial, interior, and communication design, theory fashions and the market (e.g. human-centred design, interaction design, retail design) predominate, and the rich heritage and relevance of pragmatism is poorly understood. An expanded pragmatist inquiry paradigm, incorporating visual and material argumentation and the opportunity for engagement with critical pragmatism, offers away beyond the current “conceits” of design. Such a theoretically and philosophically informed epistemology has particular relevance to the current debates about scholarship in design as it proposes a provisional metanarrative– pragmatism – as the broad epistemological and methodological base for methodological pluralism in design research and practice.